2023
DOI: 10.1055/s-0043-1770738
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Emergency Pulmonary Lobectomy under ECMO Support in Patients with COVID-19

Abstract: Background Not much is known about the results of nonelective anatomical lung resections in coronavirus disease 2019 (COVID-19) patients put on extracorporeal membrane oxygenation (ECMO). The aim of this study was to analyze the outcome of lobectomy under ECMO support in patients with acute respiratory failure due to severe COVID-19. Methods All COVID-19 patients undergoing anatomical lung resection with ECMO support at a German university hospital were included into a prospective database. Study per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Whether early thoracic surgery in the form video-assisted thoracoscopic surgery provides better clinical outcomes compared to conservative treatment still need clarification. In severe cases of COVID-19 and complicating LA, a German study reported that five of nine (55.5%) patients who underwent lobectomy under extracorporeal membrane oxygenation support died [46].…”
Section: Treatmentmentioning
confidence: 99%
“…Whether early thoracic surgery in the form video-assisted thoracoscopic surgery provides better clinical outcomes compared to conservative treatment still need clarification. In severe cases of COVID-19 and complicating LA, a German study reported that five of nine (55.5%) patients who underwent lobectomy under extracorporeal membrane oxygenation support died [46].…”
Section: Treatmentmentioning
confidence: 99%